(untitled) (Veterinary Science, 2020)
Man’s interaction with wild animals dates back to ancient times and his perception of it has been changing. Currently, society presents such a wide variety of views that make it difficult to implement conservation and management strategies without interdisciplinary work. In this context and taking into consideration the basic issues that veterinary sciences comprise, what would the contribution of the veterinarian be in the conservation and management field of wild animals?